The role of iGeneration and Silver generation in shaping sustainable food markets: a cross-generational analysis in Slovakia - Horská, Elena; Janšto, Erik; Šedík, Peter (Frontiers in Sustainable Food Systems, 2023)
The rising global phenomenon of sustainable consumption in the food market is progressively influencing a significant number of consumers on a worldwide scale. The main goal of this paper was to study consumer attitudes towards selected sustainability issues (organic aspects, animal welfare, waste management…) as well as marketing communication in the food market among two generations. Primary data were acquired by implementing online questionnaire. In total, 950 respondents participated in the survey. The results showed that iGeneration (18–25 years) has higher tendency than Silver generation (58–76 years) to support sustainability issues such as recyclable packaging, organic production and animal welfare as well as they tend to read information regarding the product nutrition and composition. The Silver generation more inclined towards Slovak origin, traditional Slovak dishes as well as they consider television and press as the main source of information. The results provide valuable insights for agrifood companies in developing consumer-driven marketing strategies. The main limitation is related to the application of self-reported measures. The future research may include cross-cultural studies as well as could be extended by incorporating other sustainability and environmental aspects.